Cannabis sativa: A comprehensive ethnopharmacological review of a medicinal plant with a long history. (5th December 2018) - Bonini, Sara Anna; Premoli, Marika; Tambaro, Simone; Kumar, Amit; Maccarinelli, Giuseppina; Memo, Maurizio; Mastinu, Andrea
Abstract: Ethnopharmacological relevance: Cannabis sativa L. ( C. sativa ) is an annual dioecious plant, which shares its origins with the inception of the first agricultural human societies in Asia. Over the course of time different parts of the plant have been utilized for therapeutic and recreational purposes, for instance, extraction of healing oils from seed, or the use of inflorescences for their psychoactive effects. The key psychoactive constituent in C. sativa is called Δ-9-tetrahydrocannabinol (D9-THC). The endocannabinoid system seems to be phylogenetically ancient, as it was present in the most primitive vertebrates with a neuronal network. N-arachidonoylethanolamine (AEA) and 2-arachidonoyl glycerol (2-AG) are the main endocannabinoids ligands present in the animal kingdom, and the main endocannabinoid receptors are cannabinoid type-1 (CB1) receptor and cannabinoid type-2 (CB2) receptor. Aim of the study: The review aims to provide a critical and comprehensive evaluation, from the ancient times to our days, of the ethnological, botanical, chemical and pharmacological aspects of C. sativa, with a vision for promoting further pharmaceutical research to explore its complete potential as a therapeutic agent. Materials and methods: This study was performed by reviewing in extensive details the studies on historical significance and ethnopharmacological applications of C. sativa by using international scientific databases, books, Master's and Ph.D. dissertations and government reports. In addition, we also try to gather relevant information from large regional as well as global unpublished resources. In addition, the plant taxonomy was validated using certified databases such as Medicinal Plant Names Services (MPNS) and The Plant List. Results and conclusions: A detailed comparative analysis of the available resources for C. sativa confirmed its origin and traditional spiritual, household and therapeutic uses and most importantly its popularity as a recreational drug. The result of several studies suggested a deeper involvement of phytocannabinoids (the key compounds in C. sativa ) in several others central and peripheral pathophysiological mechanisms such as food intake, inflammation, pain, colitis, sleep disorders, neurological and psychiatric illness. However, despite their numerous medicinal benefits, they are still considered as a menace to the society and banned throughout the world, except for few countries. We believe that this review will help lay the foundation for promoting exhaustive pharmacological and pharmaceutical studies in order to better understand the clinical relevance and applications of non-psychoactive cannabinoids in the prevention and treatment of life-threatening diseases and help to improve the legal status of C. sativa . Graphical abstract: